ELASMOBRANCH RESEARCH IN PARANÁ STATE: A FOUR-DECADE REVIEW: Pesquisa com elasmobrânquios no estado do Paraná: Uma revisão de quatro décadas - Wosnick, Natascha; Pinheiro Giareta, Eloísa; Daldin Leite, Renata; Prado, Aline Cristina; Charvet, Patricia (Arquivos de Ciências do Mar, 2023)
Abstract The present study diagnosed the state of the art of elasmobranch research in the State of Paraná, Southern Brazil. Through a systematic literature review, 220 studies with elasmobranchs in the State were retrieved. Studies began in the 1980s, reaching a peak between 2010 and 2019. When the publication categories were considered separately, a predominance of peer-reviewed papers was noted. However, when grouping grey literature categories, this type of document was predominant, indicating that many of the investigations carried out were neither peer-reviewed, nor published in indexed databases. The most representative research areas were fisheries (18%) and feeding (13%). A total of 75 species belonging to 40 genera were investigated, with most studies focused on Carcharhinus spp. (n = 60), Sphyrna spp. (n = 40), Pseudobatos spp. (n = 35), and Zapteryx brevirostris (n = 29). Some research trends in Paraná were like those identified for both South American and global scenarios, namely feeding ecology and fisheries. Nevertheless, some research areas that are key to be considered for adequate elasmobranch management and conservation measures were systematically neglected or remained underdeveloped in the State. Furthermore, for most species (e.g., Galeocerdo cuvier, Rhizoprionodon spp., Squatina spp., Narcine brasiliensis, Hypanus guttatus), information on basic biology and ecology are still lacking, indicating the need for future studies focusing on generating data for this important global elasmobranch conservation hotspot. Keywords: rays, sharks, studies, priorities, Southern Brazil.